Stock Status Assessments for 12 Exploited Fishery Species in the Tsushima Warm Current Region, Southwest Japan and East China, Using the CMSY and BSM Methods - Wang, Yuanchao; Liang, Cui; Wang, Yibang; Xian, Weiwei; Palomares, Maria Lourdes (Frontiers in Marine Science, 2020)
This contribution presents stock assessments for ten fish and two squid populations exploited by Chinese, South Korean and Japanese fishing fleets in the Tsushima Warm Current region, i.e., West of Japan and East of China. The methods used are a Monte Carlo method (CMSY) and a Bayesian state-space implementation of the Schaefer model (BSM), based on published time series of catch and abundance data (SSB and CPUE). Results show that two fish stocks, Japanese jack mackerel (Trachurus japonicus) and yellowback sea-bream (Dentex hypselosomus) are in a healthy status, while daggertooth pike conger (Muraenesox cinereus) appears to have collapsed. The other nine stocks show varying degrees of overfishing. The cooperation of several countries will be required to recovery the fishery resources in the Tsushima Warm Current region.